(untitled) (International Journal of Advanced Research in Computer Science, 2017)
In VANET GPS (Global Positioning system) is used for locating and Tracking the position of the vehicles. GPS Spoofing in the form of Transmitting False location information and denying services is an emerging threat to the VANET. It is the attack by which GPS receivers get the false navigation results and the receivers are not known about the attack. In the process of spoofing, the spoofer transmits the slightly more powerful misleading signal, stronger than the original GPS signal, fooling the receiver into using fake signals for positioning calculations. In this paper we introduce GPS spoofing detection theory using two navigators works, and to get a basic grasp of GPS spoofing detection theory and terminology. Keywords: VANET, Global positioning system, spoofing